A novel composite derived from a metal organic framework immobilized within electrospun nanofibrous polymers: An efficient methane adsorbent. (15th January 2020) - Sargazi, Ghasem; Afzali, Daryoush; Mostafavi, Ali; Kazemian, Hossein
Abstract: In this study, tantalum(V) metal organic framework (Ta‐MOF) nanostructure was incorporated within polyvinyl alcohol (PVA) nanofibers to prepare an electrospun porous composite as a novel CH4 adsorbent. The crystallinity, thermodynamic behavior, and textural properties of the products were investigated using instrumental analyses techniques. The results confirmed that the developed PVA/Ta‐MOF electrospun nanofibrous composite exhibits higher thermal stability, considerable porosity, and larger surface area compared to the parent Ta‐MOF. A 2 k factorial design was used for systematic study of the adsorption process. The results of response surface methodology (RSM) optimization indicated that the highest methane adsorption can be achieved at 24.40 °C and 3.70 bar in 23.60 min. These nano pore sorbents showed a significant potential for CH4 adsorption due to the presence of Ta‐MOF at the surface of nanofibrous composite compared to many other conventional sorbents that have been already used. This study introduces a novel biocompatible/biodegradable nanofibrous composite material with high methane adsorption performance and potentials for other applications. Abstract : A novel CH4 adsorbent with high thermal stability, high porosity, and large surface area was developed by immobilizing a metal organic framework within polyvinyl alcohol using an electrospinning technique. A 2 k factorial design was used for the systematic study of the CH4 adsorption process. RSM modeling indicated that the highest adsorption can be achieved at 24.4 °C and 3.7 bar in 23.6 min. CH4 adsorption capacity of 5.49 mmol/g was achieved under optimized conditions.